2018
DOI: 10.1088/1612-202x/aac549
|View full text |Cite
|
Sign up to set email alerts
|

High power passively Q-switched Er3+-doped ZBLAN fiber laser at 2.8 µm based on a semiconductor saturable absorber mirror

Abstract: We report a 976 nm diode-pump passively Q-switched Er3+-doped ZBLAN fiber laser based on a semiconductor saturable absorber mirror (SESAM). The maximum average output power of 3.01 W was obtained at a slope efficient of 17%. Stable passively Q-switched pulses with a pulse energy of 10.82 µJ and a pulse duration of 0.45 µs, corresponding to a peak power of 24.45 W, were obtained at a repetition rate of 278.5 kHz and a center wavelength of 2798.8 nm. To the best of our knowledge, this is the highest current aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Recently, researchers have reported that the two kinds of pulses, harmonic soliton molecules and rectangular noise-like pulses, can be coexisted in a fiber laser (Huang et al, 2016). In addition, different real saturable absorbers (SAs) can also be excellent composed for the generation of multiple pulses in the fiber laser cavity (Martinez et al, 2017; Lai et al, 2018). Other researchers reported that bound soliton and harmonic mode-locking soliton could be coexisted in an ultrafast fiber laser by MoS 2 SA for a photonic device (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have reported that the two kinds of pulses, harmonic soliton molecules and rectangular noise-like pulses, can be coexisted in a fiber laser (Huang et al, 2016). In addition, different real saturable absorbers (SAs) can also be excellent composed for the generation of multiple pulses in the fiber laser cavity (Martinez et al, 2017; Lai et al, 2018). Other researchers reported that bound soliton and harmonic mode-locking soliton could be coexisted in an ultrafast fiber laser by MoS 2 SA for a photonic device (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The SESAM provides several benefits, such as being compact, robust and free from optical alignment, and portable. [26][27][28] As an alternative to SESAM, the other saturable absorbers such as twodimensional (2D) materials, specifically, topological insulators (TIs), 2D ternary tellurides, have attracted a lot of attentions due to the virtues of low cost and ideal nonlinear optical properties. [29][30][31] Li et al added a few-layer Bi 2 Se 3 (which is a kind of TIs) saturable absorber in the ring cavity to achieve passive Q-switching, and used an un-pumped erbium-doped fiber together with a 0.06-nm-bandwidth fiber Bragg grating as an ultra-narrow filter to obtain single-frequency pulsed laser with a central wavelength of 1550 nm and a pulse duration of 2.54 µs.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the pulsed fluoride fiber lasers have been investigated to generate MIR pulse with different pulse duration via passive or active modulators with the increasing high power and high energy requirements. With the commercially available semiconductor saturable absorber mirrors (SESAMs) as saturable absorber (SA), the pulsed Er 3+doped ZBLAN fiber laser has been delivered successfully [9]. However, the SESAM suffers from the limited operation bandwidth, and the complicated and expensive manufacturing process.…”
Section: Introductionmentioning
confidence: 99%